Occurrence, metabolism, metabolic role, and industrial uses of bacterial polyhydroxyalkanoates. - Anderson, A J (1990)
Polyhydroxyalkanoates (PHAs), of which polyhydroxybutyrate (PHB) is the most abundant, are bacterial carbon and energy reserve materials of widespread occurrence. They are composed of 3-hydroxyacid monomer units and exist as a small number of cytoplasmic granules per cell. The properties of the C4 homopolymer PHB as a biodegradable thermoplastic first attracted industrial attention more than 20 years ago. Copolymers of C4 (3-hydroxybutyrate [3HB]) and C5 (3-hydroxyvalerate [3HV]) monomer units have modified physical properties; e.g., the plastic is less brittle than PHB, whereas PHAs containing C8 to C12 monomers behave as elastomers. This family of materials is the centre of considerable commercial interest, and 3HB-co-3HV copolymers have been marketed by ICI plc as Biopol. The known polymers exist as 2(1) helices with the fiber repeat decreasing from 0.596 nm for PHB to about 0.45 nm for C8 to C10 polymers. Novel copolymers with a backbone of 3HB and 4HB have been obtained. The native granules contain noncrystalline polymer, and water may possibly act as a plasticizer. Although the biosynthesis and regulation of PHB are generally well understood, the corresponding information for the synthesis of long-side-chain PHAs from alkanes, alcohols, and organic acids is still incomplete. The precise mechanisms of action of the polymerizing and depolymerizing enzymes also remain to be established. The structural genes for the three key enzymes of PHB synthesis from acetyl coenzyme A in Alcaligenes eutrophus have been cloned, sequenced, and expressed in Escherichia coli. Polymer molecular weights appear to be species specific. The factors influencing the commercial choice of organism, substrate, and isolation process are discussed. The physiological functions of PHB as a reserve material and in symbiotic nitrogen fixation and its presence in bacterial plasma membranes and putative role in transformability and calcium signaling are also considered.